THE INFLUENCE OF THINK PAIR SHARE (TPS) AS A COOPERATIVE LEARNING MODEL IN IMPROVING HEALTH INFORMATION MANAGEMENT STUDENTS’ SKILL AT DELI HUSADA DELI TUA HEALTH INSTITUTE ON TOEFL TEST - Herawati Bukit (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
TOEFL is categorized as a Norm-Referenced Test because scores are associated based on tiered counts or has percentage stages. Based on an initial survey, the biggest difficulty of TOEFL is known having high difficulty level. Think Pair Share (TPS) as a cooperative learning model for more effective learning system in providing and improving communication skills both orally and written within the scope of academic understanding through TOEFL. The application of TPS is expected to increase student's TOEFL score, learning quality and provide the opportunity to find out strategies on TOEFL success and further develop students’ skill. TPS is a type of cooperative learning designed in the form of discussion that can improve thinking skills, communication skills and encourage student participation in class. This research is aimed to improve the ability of Health Information Management students in facing TOEFL test by applying the cooperative learning model Think Pair Share (TPS). After applying the model, it found that the average score of students' TOEFL scores as well has increased from previously 56.93 to 83.68. This can be seen during the English learning process in the classroom. In learning by using Think Pair Share (TPS) model, students are required to discuss simple and effective ways to solve TOEFL questions with their friends by expressing the result of his thoughts.